2007
DOI: 10.1007/s10878-007-9045-9
|View full text |Cite
|
Sign up to set email alerts
|

Maximum k-regular induced subgraphs

Abstract: Abstract. Independent sets, induced matchings and cliques are examples of regular induced subgraphs in a graph. In this paper, we prove that finding a maximum cardinality k-regular induced subgraph is an NP-hard problem for any value of k. We propose a convex quadratic upper bound on the size of a k-regular induced subgraph and characterize those graphs for which this bound is attained. Finally, we extend the Hoffman bound on the size of a maximum 0-regular subgraph (the independence number) from k = 0 to larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 11 publications
3
37
0
Order By: Relevance
“…We note that the vertex v ∈ V (G) has degree 4 in H , the vertex v has degree 3 in H , while each vertex of P v has degree 2 in H . Let C v be the induced cycle containing P v in H , and so C v is given by vv 1 …”
Section: Theorem 1 Induced Cycle Is Np-complete For Planar Graphs Of mentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the vertex v ∈ V (G) has degree 4 in H , the vertex v has degree 3 in H , while each vertex of P v has degree 2 in H . Let C v be the induced cycle containing P v in H , and so C v is given by vv 1 …”
Section: Theorem 1 Induced Cycle Is Np-complete For Planar Graphs Of mentioning
confidence: 99%
“…Cardoso et al [1] showed that it is NP-hard to find a maximum induced r -regular subgraph of a given graph. Lozin et al [7] established efficient algorithms for special graph classes including 2P 3 -free graphs, while Moser and Thilikos [8] studied FPT-algorithms for finding regular induced subgraphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameterized complexity and exact exponential algorithms of r-MaxRIS are studied in [9] and [5], respectively. Very recently, in [2] Cardoso, Kamińsi, and Lozin prove that rMaxRIS is NP-hard for any value of r ≥ 3. Motivated by this result, we investigate the complexity of the connected version problem r-MaxRICS for r ≥ 3 in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…A convex quadratic upper bound on the order of k-regular induced subgraphs was obtained in [1] (see also [2]). In Section 3, for some connected graphs, a lower bound for the sum of squares of the entries of the principal eigenvector corresponding to the vertices of an independent set is introduced.…”
Section: Introductionmentioning
confidence: 99%